Selling war and peace Syria and the Anglosphere - Holland, Jack 1984- (Cambridge University Press, 2020)
By analysing Anglosphere foreign policy debates during the Syrian Civil War from 2011 to 2019, this book is a significant contribution to the literature in three fields. First, the book analyses the entirety of the Syrian Civil War in an innovative four-phase chronology, as the conflict evolved from calls for democracy, through chemical weapons concerns, to the rise of ISIL and the onset of Great Power proxy war. Second, the book maps and theorises Anglosphere foreign policy, charting the history and future of the US-UK-Australian military alliance during a key period of political uncertainty, defined by Donald Trump's presidency and the UK's Brexit negotiations. Third, the book develops a post-constructivist framework for the analysis of transnational political debates which determine war and peace in Syria and beyond. This framework emphasises the hard nature of soft power and the coercion of political opponents through forceful words